2012
DOI: 10.1007/s10533-011-9691-y
|View full text |Cite
|
Sign up to set email alerts
|

Tidal exchange of total mercury and methylmercury between a salt marsh and a Chesapeake Bay sub-estuary

Abstract: We examined the net exchange of total mercury (THg) and methylmercury (MeHg) between a tidal marsh and its adjacent estuary over a 1-year period from August 2007 to July 2008. Our objectives were to estimate the importance of tidal salt marshes as sources and sinks of mercury within the Chesapeake Bay system, and to examine the hydrologic and biogeochemical controls on mercury fate and transport in tidal marshes. Tidal flows and water chemistry were measured at an established tidal flume at the mouth of the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 55 publications
0
14
3
Order By: Relevance
“…Previous studies reported that MeHg levels in surface water ranged from 0.003 to 0.4 ng/L for tidal marshes in the estuary 22,24,44,45 and 0.008 to 0.6 ng/L for other estuarine wetlands. 29,31 Reported groundwater MeHg levels ranged from 0.008 to 4.0 ng/L. 31,44 In this study, large variations in the fraction of MeHg/THg were measured in both surface water (0.08−5%) and groundwater (0.02−1%) across different sampling locations and times.…”
Section: ■ Results and Discussionmentioning
confidence: 64%
“…Previous studies reported that MeHg levels in surface water ranged from 0.003 to 0.4 ng/L for tidal marshes in the estuary 22,24,44,45 and 0.008 to 0.6 ng/L for other estuarine wetlands. 29,31 Reported groundwater MeHg levels ranged from 0.008 to 4.0 ng/L. 31,44 In this study, large variations in the fraction of MeHg/THg were measured in both surface water (0.08−5%) and groundwater (0.02−1%) across different sampling locations and times.…”
Section: ■ Results and Discussionmentioning
confidence: 64%
“…Differences in BAF were most evident at sites associated with large coastal marsh areas (BH, BI, PC) and those having the largest differences in DOC concentration (BH and BI). While DOC increases the solubility and stability of MeHg in the water column in estuaries (Bergamaschi et al, 2011;Mitchell et al, 2012), it also decreases the bioavailability of MeHg at the base of the foodweb (Lee and Fisher, 2017;Luengen et al, 2012). Differences in DOC quality have been suggested to effect MeHg bioavailability, where humic fractions of terrestrial or wetland-derived DOC have been found to form DOC-MeHg complexes with low bioavailability (Schartup et al, 2015b).…”
Section: Discussionmentioning
confidence: 99%
“…In streams, concentrations of MeHg have been found to correlate with DOC across a wide range of sites (Tsui and Finlay, 2011), although the relationship is less clear across time points because MeHg concentrations vary temporally (Chasar et al, 2009). MeHg concentrations in estuaries also vary temporally throughout the year (Mitchell et al, 2012), but have been found to associate across tidal cycles (Bergamaschi et al, 2011). While MeHg and DOC were correlated in intertidal waters, differences in watershed and marine inputs, and the extent of mixing between sites contribute to changing correlations between tides.…”
Section: Discussionmentioning
confidence: 99%
“…The increased MeHg production in managed freshwater reservoirs and wetlands should not be assumed for estuarine tidal marshes that undergo wetting and drying on a diurnal basis, due to differences in hydrodynamics, frequency, and geochemistry. For example, in a comprehensive study of THg and MeHg flux from a Chesapeake Bay tidal marsh in Maryland, USA, Mitchell et al () reported that the marsh was a net sink for THg and a relatively small net source of MeHg to the estuary, primarily during the growing season.…”
Section: Mercury Cycling In the Environmentmentioning
confidence: 99%